Silencing of NAC1 Expression Induces Cancer Cells Oxidative Stress in Hypoxia and Potentiates the Therapeutic Activity of Elesclomol - Ren, Yi-Jie; Wang, Xiao-Hui; Ji, Cheng; Guan, Yi-Di; Lu, Xian-Jiu; Liu, Xian-Rong; Zhang, Hong-Han; Guo, Ling-Chuan; Xu, Qiong-Hua; Zhu, Wei-Dong; Ming, Zhi-Jun; Yang, Jin-Ming; et al. (Frontiers in Pharmacology, 2017)
In order to survive under conditions of low oxygen, cancer cells can undergo a metabolic switch to glycolysis and suppress mitochondrial respiration in order to reduce oxygen consumption and prevent excessive amounts of reactive oxygen species (ROS) production. Nucleus accumbens-1 (NAC1), a nuclear protein of the BTB/POZ gene family, has pivotal roles in cancer development. Here, we identified that NAC1-PDK3 axis as necessary for suppression of mitochondrial function, oxygen consumption, and more harmful ROS generation and protects cancer cells from apoptosis in hypoxia. We show that NAC1 mediates suppression of mitochondrial function in hypoxia through inducing expression of pyruvate dehydrogenase kinase 3 (PDK3) by HIF-1α at the transcriptional level, thereby inactivating pyruvate dehydrogenase and attenuating mitochondrial respiration. Re-expression of PDK3 in NAC1 absent cells rescued cells from hypoxia-induced metabolic stress and restored the activity of glycolysis in a xenograft mouse model, and demonstrated that silencing of NAC1 expression can enhance the antitumor efficacy of elesclomol, a pro-oxidative agent. Our findings reveal a novel mechanism by which NAC1 facilitates oxidative stress resistance during cancer progression, and chemo-resistance in cancer therapy.